Mapping Research Trends on Technology and Artificial Intelligence in Islamic Education: A Bibliometric Analysis of Scopus Database (2019–2025) - Muhammad Wahyudi Azzukhruf (ITScience (Information Technology and Science), 2025)
The integration of Artificial Intelligence (AI) into Islamic education institutions reflects a shift from basic digital adoption toward more advanced technological applications. This study examines the development of research on technology and AI in Islamic education using data from the Scopus database. Bibliographic records published between 2019 and 2025 were collected using a set of predefined keywords and refined through several filtering limitations, resulting in a dataset of 222 documents. Bibliometric analysis was conducted using VOSviewer, focusing on publication trends, country contributions, and keyword co-occurrence through network, overlay, and density visualizations. The results indicate a moderate growth in publications during 2019–2021, followed by a marked increase from 2022 to 2025. Indonesia and Malaysia emerge as the most prolific contributors, reflecting the prominence of this topic within regional institutional contexts. The analysis also identifies a thematic shift from the use of basic digital learning tools during the pandemic period to discussions on AI integration, institutional management in Pesantren (Islamic boarding schools), and ethical considerations in more recent literature. While studies on general e-learning effectiveness appear to be saturated, limited attention has been given to the ethical alignment of AI with Islamic values. Therefore, future research should place greater emphasis on the development of ethical frameworks that integrate AI with Islamic educational principles.